a Pengembangan E-Modul Praktikum Kimia Berbasis Green Chemistry pada Materi Laju Reaksi - Sayyidatuzzahrah, Erza; Sofia, Baiq Fara Dwirani; siahaan, Jackson (FKIP University of Mataram, 2025)
The current researchnis airesearchiandidevelopmentistudyithat aimsitoidetermine the validity, practicality andieffectivity of chemistry practicum e-module based of green chemistry onireactionirate topic that was developed. This research used 4D research and developments model (define, design, develop and disseminate). The sample in this research was 24 students class XI MIPA at SMAN 1 Gerung. The result showed that validity obtained using the Aiken’s V = 0,9 showed that the chemistry practicum e-module based of green chemistry on reaction rate topic is very valid. Practicality seen through the student response questionnaire as a user. Obtained an average practicality value of 91% showed that the chemistry practicum e-module based of green chemistry on reaction rate topic is very practical. While for the effectivity based on N-Gain score obtained an average of 0,71, it showed that the chemistry practicum e-module based of green chemistry on reaction rate topic is very effective in improving students learning outcomes on reaction rate topic.